Gothic Theory and Aesthetics: Transdisciplinary Landscapes in Film, Theatre, Architecture and Literature - Corrêa, Graça P. (2021)
This book presents a transdisciplinary approach to the Gothic-Romantic legacy in different artistic media, revealing how theatre, performance,  lm, literature, visual arts and architecture intersect in the construction of theoretical and aesthetic landscapes. Through an ethical-political and ecophilosophical assessment, it contributes towards a much-needed reevaluation of the Gothic-Romantic mode in the  eld of Art Studies, at a time of widespread popularity of Gothiclike imagery in global contemporary cultural production. The Gothic-Romantic tradition mapped here is broad, addressing philosophical concepts and devised theatre experiences; literary works by Alexandre Herculano, E.T.A. Hoffmann, Edgar Allan Poe, J. W. Goethe, Friedrich Schiller, Percy Shelley and Alexandre Dumas père;  lms by Alfred Hitchcock, Stanley Kubrick, Lars von Trier, David Lynch, Alejandro Amenábar and Guillermo del Toro; architectural and visual design by Horace Walpole, William Beckford and Luigi Manini (Quinta da Regaleira, Portugal).